Love me, love me not. Vol. 1 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2020)
"Fast friends Yuna and Akari are complete opposites--Yuna is an idealist, while Akari is a realist. When lady-killer Rio and the oblivious Kazuomi join their ranks, love and friendship become quite complicated!"--Provided by publisher.